Functional analyses of ATM, ATR and Fanconi anemia proteins in lung carcinoma. Issue 1 (December 2015) - Beumer, Jan; Fu, Katherine; Anyang, Bean; Siegfried, Jill; Bakkenist, Christopher
Abstract Background ATM and ATR are kinases implicated in a myriad of DNA-damage responses. ATM kinase inhibition radiosensitizes cells and selectively kills cells with Fanconi anemia (FA) gene mutations. ATR kinase inhibition sensitizes cells to agents that induce replication stress and selectively kills cells withATM andTP53 mutations.ATM mutations andFANCF promoter-methylation are reported in lung carcinomas. Methods We undertook functional analyses of ATM, ATR, Chk1 and FA proteins in lung cancer cell lines. We included Calu6 that is reported to be FANCL-deficient. In addition, the cancer genome atlas (TCGA) database was interrogated for alterations in: 1)ATM, MRE11A, RAD50 andNBN ; 2)ATR, ATRIP andTOPBP1 ; and 3) 15 FA genes. Results No defects in ATM, ATR or Chk1 kinase activation, or FANCD2 monoubiquitination were identified in the lung cancer cell lines examined, including Calu6, and major alterations in these pathways were not identified in the TCGA database. Cell lines were radiosensitized by ATM kinase inhibitor KU60019, but no cell killing by ATM kinase inhibitor alone was observed. While no synergy between gemcitabine or carboplatin and ATR kinase inhibitor ETP-46464 was observed, synergy between gemcitabine and Chk1 kinase inhibitor UCN-01 was observed in 54 T, 201 T and H460, and synergy between carboplatin and Chk1 kinase inhibitor was identified in 201 T and 239 T. No interactions between ATM, ATR and FA activation were observed by either ATM or ATR kinase inhibition in the lung cancer cell lines. Conclusions Analyses of ATM serine 1981 and Chk1 serine 345 phosphorylation, and FANCD2 monoubiquitination revealed that ATM and ATR kinase activation and FA pathway signaling are intact in the lung cancer cell lines examined. As such, these posttranslational modifications may have utility as biomarkers for the integrity of DNA damage signaling pathways in lung cancer. Different sensitization profiles between gemcitabine and carboplatin and ATR kinase inhibitor ETP-46464 and Chk1 kinase inhibitor UCN-01 were observed and this should be considered in the rationale for Phase I clinical trial design with ATR kinase inhibitors.